2020
DOI: 10.3390/met10111466
|View full text |Cite
|
Sign up to set email alerts
|

EBSD Study of Delta-Processed Ni-Based Superalloy

Abstract: Nickel-based superalloys are extensively used in the aerospace and power generation industries due to their excellent mechanical properties at elevated temperatures and good corrosion resistance. Typically, these alloys require accomplishing critical standards during their manufacturing process. In this study, an Inconel 718 (IN718) Ni-based superalloy was subjected to a delta-processing treatment (DP718) and subsequently deformed at high temperature. Samples were compressed below and above the δ-solvus temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The intentional δ-phase precipitation cycle, in preparation for subsequent DP718 thermomechanical processing, may control excessive grain growth during hot deformation and may produce a uniform microstructure with ASTM grain sizes primarily ranging from 6 (45μm), 5 (63μm), 4 (90μm) as can be seen in previous reports [10,27,28]. Figure 3 shows the metallographic OM images after double impact hot deformation steps for 50, 500, 5000 s of interpass times between the first and the second deformation steps at a strain rate of 0.1 s -1 of the samples tested at 900, 925, 950, 975 and 1000 °C.…”
Section: 2) Microstructural Characterizationmentioning
confidence: 85%
“…The intentional δ-phase precipitation cycle, in preparation for subsequent DP718 thermomechanical processing, may control excessive grain growth during hot deformation and may produce a uniform microstructure with ASTM grain sizes primarily ranging from 6 (45μm), 5 (63μm), 4 (90μm) as can be seen in previous reports [10,27,28]. Figure 3 shows the metallographic OM images after double impact hot deformation steps for 50, 500, 5000 s of interpass times between the first and the second deformation steps at a strain rate of 0.1 s -1 of the samples tested at 900, 925, 950, 975 and 1000 °C.…”
Section: 2) Microstructural Characterizationmentioning
confidence: 85%
“…GB wetting by the second solid phase can have a strong influence on the properties of materials, including Al alloys [18,20,22,23,[25][26][27][28][29][30][31][32][33][34][35], Fe-based alloys and steels [36,, Co-and Ni-based alloys [78][79][80][81][82][83][84][85], Cu alloys [86,88,90], Ti-and Zr-based alloys [91,93,95,97,, Mg alloys [124,126,[128][129][130][131], as well multicomponent and high-entropy alloys [132,134,[136][137][138][139][140][141][142][143][144].…”
Section: Influence Of Gb Wetting By the Second Solid Phase On The Pro...mentioning
confidence: 99%
“…The decreased cleavage size, in turn, increased ductility [80]. The high-temperature oxidation behavior induced by precipitation in a Ni-Y-Al alloy is also controlled by the wetting of interfaces [82] [79], in a Ni-Y-Al alloy after high-temperature oxidation [82], in the (Ti 45 Ni 55 ) 100−x Fe x (x = 0.5, 1, 3, 5 at%) alloy containing X-phase precipitates and having high hardness and high compressive strength [85], the Invar/Cu bimetal composites [88], NiTi superelastic alloy manufactured by selective laser melting [115], Cu based Ti 2 AlC composite [91] as well as in Bi-containing brass (Cu-3wt%Bi-30wt%Zn) [90]. The transition between discontinuous and continuous precipitation of the Cr-rich phase was observed by the annealing of solution-treated binary Ni-Cr alloys with 30%, 35%, 40%, 45%, and 50% Cr, and ternary ones doped by 0.5% third elements (Cu, Zr, Nb, Fe, and B) [81].…”
Section: Influence Of Gb Wetting By the Second Solid Phase On The Pro...mentioning
confidence: 99%
See 1 more Smart Citation
“…Mayo et al [2] shown a combination of interrupted tensile tests with crystallographic characterization performed by means of EBSD, by analyzing the evolution of an intercritically deformed micro-alloyed steel. Kanetas et al [3] performed a detailed microstructural characterization by the EBSD of Inconel 718 (IN718) Ni-based superalloy that was subjected to a delta-processing treatment (DP718) and, subsequently, deformed at high temperature. Gondo et al [4] studied the evolution of texture in the thickness direction of the cylindrical cup, which was spun from a rolled aluminum sheet in 13 passes, using electron backscatter diffraction pattern analysis.…”
Section: Contributionsmentioning
confidence: 99%